2012
DOI: 10.2215/cjn.04250511
|View full text |Cite
|
Sign up to set email alerts
|

Venous Thromboembolism in Patients with Membranous Nephropathy

Abstract: SummaryBackground and objectives The aims of this study were to determine the frequency of venous thromboembolic events in a large cohort of patients with idiopathic membranous nephropathy and to identify predisposing risk factors.Design, setting, participants, & measurements We studied patients with biopsy-proven membranous nephropathy from the Glomerular Disease Collaborative Network (n=412) and the Toronto Glomerulonephritis Registry (n=486) inception cohorts. The cohorts were pooled after establishing simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
148
3
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(169 citation statements)
references
References 49 publications
(34 reference statements)
9
148
3
8
Order By: Relevance
“…The frequency of VTE observed in this study is consistent with what has previously been described in the nephrotic syndrome associated with membranous nephropathy 11,12 and with what has been reported in AL and multiple myeloma. 5,24,25 Interestingly, no renal vein thromboses were documented in this group; this may reflect the often clinically silent nature of these events, which have been observed in as many as 40-50% of patients with nephrotic syndrome, 15 but were not screened for in our population.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The frequency of VTE observed in this study is consistent with what has previously been described in the nephrotic syndrome associated with membranous nephropathy 11,12 and with what has been reported in AL and multiple myeloma. 5,24,25 Interestingly, no renal vein thromboses were documented in this group; this may reflect the often clinically silent nature of these events, which have been observed in as many as 40-50% of patients with nephrotic syndrome, 15 but were not screened for in our population.…”
Section: Discussionsupporting
confidence: 92%
“…[26][27][28][29] The association between low serum albumin and risk of VTE has been previously described in nephrotic syndrome. 11,12,14,30 Serum albumin is inversely correlated with the degree of urinary protein loss, and may be a surrogate marker for loss of endogenous antithrombotic proteins such as antithrombin III and plasminogen. Serum albumin levels may have direct effects on hemostasis and platelet aggregation 26 and in addition levels may be decreased in critical illness and thus correlate with more advanced disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acute renal vein thrombosis is usually characterized by a recent episode of acute flank pain, macroscopic hematuria, flank tenderness at percussion, worsening proteinuria, and deterioration of renal function (45). Hypoalbuminemia, particularly a serum albumin concentration ,2.8 g/dl, is the most significant independent predictor of venous thrombotic risk in patients with MN (46). In view of the above, it is unlikely that our patient had developed acute renal vein thrombosis, although asymptomatic chronic renal vein thrombosis cannot be ruled out.…”
Section: Discussion Of Questionmentioning
confidence: 73%
“…Of all of the nephrotic syndrome etiologies, for reasons heretofore unexplained, MN is associated with the greatest risk for clot, with some series citing up to a 35% lifetime risk for clot for patients with MN (16,17). In the largest cohort of patients with MN studied to date combining United States (n=412) and Canadian (n=486) patients, Lionaki et al (17) showed that the risk of thrombotic events in MN increased significantly when serum albumin levels fall below 2.8 g/dl. Therefore, this patient with MN and a serum albumin of 2.6 g/dl would be considered high risk for a clotting complication, but there is no consensus agreement on whether such patients should be offered prophylactic anticoagulation (choice C).…”
Section: Discussion Of Question 1bmentioning
confidence: 99%